2008
DOI: 10.1021/es801246c
|View full text |Cite
|
Sign up to set email alerts
|

Controls on Metal Leaching from Secondary Pb Smelter Air-Pollution-Control Residues

Abstract: Air-pollution-control (APC) residues are among the most toxic waste materials from secondary Pb metallurgy. Two distinct APC residues collected from bag-type filters of one Czech secondary Pb smelter were subjected to leaching experiments to determine the mineralogical and geochemical controls on leaching of metallic contaminants (Cd, Cu, Pb, Zn). A kinetic 720-h leaching test in deionized water at a liquid-to-solid (L/S) ratio of 10 L kg(-1) and a 48-h leaching test at various L/S ratios (0.5, 1, 5, 10, 50, 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
63
1

Year Published

2009
2009
2022
2022

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 41 publications
(72 citation statements)
references
References 21 publications
8
63
1
Order By: Relevance
“…This could be attributed to the more mobile property of Cd and Pb than Zn in the environment (Podlesakova et al 2001), especially those affected by Zn smelting. Leaching experiments of air-pollution-control residues from smelting also indicated a more mobile feature of Cd than Pb and Zn (Ettler et al 2008). Even though enrichment factors of Pb and Zn varied, a very close correlation between Pb and Zn in samples can be computed (R 2 =0.805, p<0.01).…”
Section: Resultsmentioning
confidence: 92%
“…This could be attributed to the more mobile property of Cd and Pb than Zn in the environment (Podlesakova et al 2001), especially those affected by Zn smelting. Leaching experiments of air-pollution-control residues from smelting also indicated a more mobile feature of Cd than Pb and Zn (Ettler et al 2008). Even though enrichment factors of Pb and Zn varied, a very close correlation between Pb and Zn in samples can be computed (R 2 =0.805, p<0.01).…”
Section: Resultsmentioning
confidence: 92%
“…The dispersal of contaminants in the vicinity of mines and smelters is highly dependent on the local meteorological conditions, mainly on the prevailing wind direction (Ettler et al, 2005aKříbek et al, 2010). In addition, dust emitted by the smelters generally consists of fine-grained materials with extremely high specific surface area and high solubility, whereas particles generated by ore crushers in mining areas are generally larger in size (Ettler et al, 2005b(Ettler et al, , 2008Kříbek et al, 2010). Thus, the areas affected by smelterderived particles are generally larger than areas polluted by mining activities (Figs.…”
Section: Spatial Distribution and Bioaccessibility Of As And Metals Imentioning
confidence: 99%
“…In contrast, the smelter dusts are generally composed of more soluble metal-bearing compounds (Ettler et al, 2005b(Ettler et al, , 2008. Recent investigations of the pH-dependent leaching behaviour of the copper smelter flue dust from one smelter in the Zambian Copperbelt indicated that primary chalcanthite (CuSO 4 ·5H 2 O) was readily dissolved, especially under acidic conditions and large amounts of Cu were released (Vítková et al, 2011).…”
Section: Spatial Distribution and Bioaccessibility Of As And Metals Imentioning
confidence: 99%
“…Qualitative analysis was performed with the X'Pert HighScore software 1.0 equipped with the ICDD PDF-2 database [14]. The results exclude the possible presence of amorphous admixtures, which were suggested by Ettler et al [15]. Quantitative determination of the phases (%) was performed by means of the Rietveld procedure using the Topas 3 software supplemented with the ICSD database [16].…”
Section: Solid-phase Analysismentioning
confidence: 99%